2020
DOI: 10.3390/molecules25071694
|View full text |Cite
|
Sign up to set email alerts
|

Induced Wide Nematic Phase by Seven-Ring Supramolecular H-Bonded Systems: Experimental and Computational Evaluation

Abstract: New seven-ring systems of dipyridine derivative liquid crystalline 2:1 supramolecular H-bonded complexes were formed between 4-n-alkoxyphenylazo benzoic acids and 4-(2-(pyridin-4-yl)diazenyl)phenyl nicotinate. Mesomorphic behaviors of the prepared complexes were investigated using a combination of differential scanning calorimetry (DSC) and polarizing optical microscopy (POM). Fermi bands attributed to the presence of intermolecular H-bond interactions were confirmed by FT–IR spectroscopy. All prepared complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Several H-bond liquid crystals exhibit rapid photoresponses and the broad-range blue phase, showing potential applications in organic optoelectronics as sensors or optical gates. Very recently, several new types of AzPy-containing supramolecular liquid crystals with different geometries were reported, e.g., rod-like shape [33,45,46], chair/V-shape [47,48], and taper-shape [49] as well as bent-shape [49,50]. It was suggested that the chairshaped conformers were more stable than the V-shaped isomeric complexes [47].…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Several H-bond liquid crystals exhibit rapid photoresponses and the broad-range blue phase, showing potential applications in organic optoelectronics as sensors or optical gates. Very recently, several new types of AzPy-containing supramolecular liquid crystals with different geometries were reported, e.g., rod-like shape [33,45,46], chair/V-shape [47,48], and taper-shape [49] as well as bent-shape [49,50]. It was suggested that the chairshaped conformers were more stable than the V-shaped isomeric complexes [47].…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Recently, we employed theoretical calculations to correlate experimental ones regarding liquid crystalline materials [62][63][64][65][66][67][68][69][70][71][72][73]. Thus, DFT calculations were conducted for the basis set, B3LYP 6-311g (d, p), for all the supramolecular analogous series of the complexes that were prepared with p-octyloxy benzoic acid ((I-V)C8).…”
Section: Theoretical Calculations (Dft) Molecular Geometrymentioning
confidence: 99%
“…Recently, many researchers [5,31,[44][45][46][47][48][49][50][51][52][53][54] have reported the mesophase characteristics of new supramolecular H-bonded complexes (SMHBCs) between acids and pyridines as base one [55,56]. In order to better understand the structural effect relationship of SMHBC-based azopyridines, two groups of H-bonded complexes (1:2) based on pyridine as the H-acceptor were investigated [55,57,58]. In another study, the 1:1 SMHBCs prepared between the nitrogen atom of the azomethine derivative and 4-alkoxybenzoic acids [59] has been reported and characterized.…”
Section: Introductionmentioning
confidence: 99%